PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT SEMESTANUSTRA DISTRINDO, TANJUNG MORAWA – DELI SERDANG - Dania, Eva; Liaufaldi, Nurjafa; Ciamas, Elserra Siemin (Jurnal KAFEBIS, 2024)
PT Semestanustra Distrindo, Tanjung Morawa - Deli Serdang is a trading company that sells various kinds of biscuits and snacks. This company sells in the form of consignment sales where consignment is: sales are made by entrusting goods to an outlet that acts as a selling agent but the rights to the goods remain in the hands of the owner until sold. The purpose of this research is to determine the influence of product quality on purchasing decisions. The method used in this research is descriptive method, this type of research is quantitative data, primary data obtained through questionnaires. The research population that will be used in the research is all consumers who made purchases from the company during the 2020 period, totaling 204 consumers. Because the population used is 204 consumers, the population will be reduced using the Slovin sampling technique with a confidence level of 95% and an error rate of 5%, where 135 samples are obtained. The analysis technique used is simple linear analysis and statistical tests, namely t-test (partial) using SPSS (statistical package for the social sciences) software. The test results show that product quality partially has a positive and significant effect on consumer purchasing decisions.